Analisis Kemampuan Berpikir Kritis Matematis dalam Menyelesaikan Soal Materi Perbandingan Ditinjau dari Self Efficacy - Al-Islami, Saniyati; Prihatin, Iwit; Hartono, Hartono (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study examines the correlation between mathematical critical thinking skills and self efficacy in students of Class VIII at SMP Negeri 1 Suti Semarang. The objective is to assess students’ ability to solve ratio problems, viewed through different levels of self efficacy: high, medium, and low. Using a qualitative descriptive method, the research involves data collection through self efficacy questionnaires, critical thinking tests, and interviews. The data produced were analyzed quantitatively and qualitatively. The findings indicate that students with higher self efficacy demonstrate stronger critical thinking abilities, while those with lower self efficacy struggle more with critical thinking indicators. These insights may help in devising strategies to determine both self efficacy and critical thinking skills in mathematics education